The use of commercial arbitration rules in investment treaty disputes : domestic courts, commercial arbitration institutions and tribunal jurisdiction - Dahlquist Cullborg, Joel, 1987- (International litigation in practice, 2021)
"Arbitration clauses in investment treaties often provide investors with a choice between ICSID arbitration, on the one hand, and rules originally drafted for commercial arbitration on the other. The Use of Commercial Arbitration Rules in Investment Treaty Disputes studies how domestic courts and commercial arbitration institutions impact the scope of arbitral tribunal jurisdiction when commercial arbitration rules are used. Based on extensive studies of court decisions and previously-unknown arbitral awards, Joel Dahlquist's book analyses the practice of domestic courts in reviewing treaty-based jurisdiction, and explains how the two most used commercial arbitration institutions - the ICC and the SCC - have drafted, interpreted and applied their arbitration rules in treaty-based disputes"--